Comparative Analysis of Marketing Channels of Cayenne Pepper Through Auction Market and Other Channels in Turi District, Sleman Regency - Mahendra, Yusuf Iqbal; Rifin, Amzul; Rosiana, Nia (Jurnal Manajemen & Agribisnis, 2023)
Turi District is one of cayenne pepper production areas in Sleman Regency. The marketing of Cayyene Pepper is interesting to study especially after the chili auction market was established in Sleman Regency in 2018. Therefore, this study aims to compare the marketing of cayenne pepper through the auction market marketing channel with other marketing channels in Sleman Regency based on marketing margin, farmer’s share, and profit ratio to marketing cost. The data collection methods were purposive sampling method applied on farmers and snowball sampling method applied on marketing organization. The results showed that the marketing of cayenne pepper in Turi District, Sleman Regency in 2022 has five marketing channels, namely the auction market, collectors, wholesalers and traders. In addition, the marketing agencies involved have carried out the existing marketing functions, that is the exchange function, physical function and facility function. Basically, channel III through large traders has a quantitative indicator value of marketing efficiency that is better than channel I. Meanwhile, for local market destinations channel II has a better efficiency indicator value than channel IV which goes through small collectors. Keywords: auction market, cayenne pepper, marketing channels, marketing efficiency, marketing functions